INDIRECT REGENERATION OF CURCUMA LONGA L (VARIETY SUGUNA) FROMIN-VITRODERIVED LEAFCALLUS - Suresh Kumar C1., Akhila A2., Mohan Kumar B. S3.,Keshamma E4*, (Chelonian Research Foundation, 2023)
Turmeric (Curcuma longa) is one of the oldest and most important spices known for its distinctflavour and its numerous medicinal properties. This vital spice is inflicted by various diseases and pests; and none of the cultivars are resistant. Therefore, the conservation of the Curcuma longagene pool is important. In response to this requirement, an attempt has been made in the present study, to induce callus formation using in-vitro derived leaf of Curcuma longa (variety suguna) on Linsmaier and Skoog basal medium(LSBM) fortified with 2,4-Dichlorophenoxy acetic acid (2,4-D).The callus was then cultured and sub culturedoverLSBM supplemented with combinations of 2 Isopentenyl adenine (2-iP), 6-Benzylaminopurine(BAP)with 2,4-Dichlorophenoxy acetic acid to obtain multiple shoots. Our results delineatedthat 2-iP and BAP exhibited a synergistic effect on the indirect regeneration of Curcuma longa (varietysuguna) derived from in-vitroleafcallus. Keywords: leaf callus, plant regeneration,Curcuma longa,6-Benzylaminopurine(BAP) and 2,4-Dichlorophenoxy acetic acid(2,4-D)